Additive manufacturing of liquid/gas diffusion layers for low-cost and high-efficiency hydrogen production. (30th January 2016) - Mo, Jingke; Dehoff, Ryan R.; Peter, William H.; Toops, Todd J.; Green, Johney B.; Zhang, Feng-Yuan
Abstract: A low-cost additive manufacturing technology, electron beam melting (EBM), is employed for the first time to fabricate titanium liquid/gas diffusion media with high-corrosion resistances and well-controlled multifunctional parameters, including two-phase transport and high electric/thermal conductivities. Its application in proton exchange membrane electrolyzer cells (PEMECs) has been investigated in-situ with modular galvano (MG) and galvano electrochemical impedance spectroscopy (GEIS) and characterized ex-situ with SEM and XRD. Compared with conventional woven and sintered liquid/gas diffusion layers (LGDLs), much better performance is obtained with EBM-fabricated LGDLs due to a significant reduction of ohmic losses. The EBM technology components exhibited several distinct advantages in fabricating LGDLs: well-controllable pore morphology and structure, rapid prototyping, fast manufacturing, highly customizable design, and economic. In addition, by taking advantage of additive manufacturing, it is possible to fabricate complicated three-dimensional designs of virtually any shape from a digital model into one single solid object faster, cheaper, and easier, especially for titanium components. More importantly, this development will provide LGDLs with well-controllable pore morphologies, which will be valuable to develop sophisticated models of PEMECs with optimal and repeatable performance. Furthermore, it could lead to a manufacturing solution that greatly simplifies the PEMEC/fuel cell components. Highlights: A first report of low-cost additive manufacturing of titanium liquid/gas diffusion media. A fast and economic way to fabricate the prototype of new PEMEC components. Multifunctional LGDLs are successfully fabricated for the first time with EBM additive manufacturing technique. Significant reduction of the ohmic loss and promotion of the PEMEC performance. A manufacturing solution to simplify PEMEC/FC components and to reduce the cost.